A feasibility trial to examine the social norms approach for the prevention and reduction of licit and illicit drug use in European University and college students - Pischke Claudia R; Zeeb Hajo; van Hal Guido; Vriesacker Bart; McAlaney John; Bewick Bridgette M; Akvardar Yildiz; Guillén-Grima Francisco; Orosova Olga; Salonna Ferdinand; Kalina Ondrej; Stock Christiane; et al. (BMC, 2012)
Abstract Background Incorrect perceptions of high rates of peer alcohol and tobacco use are predictive of increased personal use in student populations. Correcting misperceptions by providing feedback has been shown to be an effective intervention for reducing licit drug use. It is currently unknown if social norms interventions are effective in preventing and reducing illicit drug use in European students. The purpose of this paper is to describe the design of a multi-site cluster controlled trial of a web-based social norms intervention aimed at reducing licit and preventing illicit drug use in European university students. Methods/Design An online questionnaire to assess rates of drug use will be developed and translated based on existing social norms surveys. Students from sixteen universities in seven participating European countries will be invited to complete the questionnaire. Both intervention and control sites will be chosen by convenience. In each country, the intervention site will be the university that the local principal investigator is affiliated with. We aim to recruit 1000 students per site (baseline assessment). All participants will complete the online questionnaire at baseline. Baseline data will be used to develop social norms messages that will be included in a web-based intervention. The intervention group will receive individualized social norms feedback. The website will remain online during the following 5 months. After five months, a second survey will be conducted and effects of the intervention on social norms and drug use will be measured in comparison to the control site. Discussion This project is the first cross-national European collaboration to investigate the feasibility of a social norms intervention to reduce licit and prevent illicit drug use among European university students. Final trial registration number DRKS00004375 on the 'German Clinical Trials Register'.